Stigma associated with genetic testing for rare diseases—causes and recommendations - Baynam, Gareth; Gomez, Roy; Jain, Ritu (Frontiers in Genetics, 2024)
Rare disease (RD) is a term used to describe numerous, heterogenous diseases which are geographically disparate. Approximately 400 million people worldwide live with a RD equating to roughly 1 in 10 people, with 71.9% of RDs having a genetic origin. RDs present a distinctive set of challenges to people living with rare diseases (PLWRD), their families, healthcare professionals (HCPs), healthcare system, and societies at large. The possibility of inheriting a genetic disease has a substantial social and psychological impact on affected families. In addition to other concerns, PLWRD and their families may feel stigmatized, experience guilt, feel blamed and stress about passing the disease to future generations. Stigma can affect all stages of the journey of PLWRD and their families, from pre-diagnosis to treatment access, care and support and compliance. It adversely impacts the quality of life of RD patients. To explore impact of stigma associated with genetic testing for RDs better, we conducted a literature search on PubMed and Embase databases to identify articles published on stigma and rare diseases between January 2013 to February 2023. There is a dearth of literature investigating the dynamics of stigma and RD genetic testing. The authors observed that the research into the implications of stigma for patient outcomes in low-and middle-income countries (LMICs) and potential interventions is limited. Herein, the authors present a review of published literature on stigma with a focus on RD genetic testing, the associated challenges, and possible ways to address these.